Causal Misperceptions of the Part-Time Pay Gap - Annekatrin Schrenker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
This paper studies if workers infer from correlation about causal effects in the context of the part-time wage penalty. Differences in hourly pay between full-time and part-time workers are strongly driven by worker selection and systematic sorting. Ignoring these selection effects can lead to biased expectations about the consequences of working part-time on wages (`selection neglect bias'). Based on representative survey data from Germany, I document substantial misperceptions of the part-time wage gap. Workers strongly overestimate how much part-time workers in their occupation earn per hour, whereas they are approximately informed of mean full-time wage rates. Consistent with selection neglect, those who perceive large hourly pay differences between full-time and part-time workers also predict large changes in hourly wages when a given worker switches between full-time and part-time employment. Causal analyses using a survey experiment reveal that providing information about the raw part-time pay gap increases expectations about the full-time wage premium by factor 1.7, suggesting that individuals draw causal conclusions from observed correlations. De-biasing respondents by informing them about the influence of worker characteristics on observed pay gaps mitigates selection neglect. Subjective beliefs about the part-time/full-time wage gap are predictive of planned and actual transitions between full-time and part-time employment, necessitating the prevention of causal misperceptions.
Keywords: J31; D83; D84; 330; part-time pay gap; wage expectations; selection neglect; causal misperceptions